Factors influencing nursing home placement of patients with dementia: a retrospective, single‐centre study in Japan. Issue 2 (8th October 2018) - Ota, Kazumi; Arikawa, Masatoshi; Ohashi, Shizuko; Azekawa, Takaharu; Matsumoto, Toshihiko
Abstract : Aim: This was an exploratory study to examine the factors influencing nursing home placement (NHP) in Japan. Methods: For this analysis, 633 patients were selected. The data were collected from the clinical records of each patient. A log‐rank test was performed. The time from the patient's first visit to the clinic until the nursing home placement was the independent variable. Age (<80 or ≥80 years), biological sex (male or female), Clinical Dementia Rating scale (CDR) score (overall index 0.5, 1, 2, or 3), living situation (living alone or with someone), and voxel‐based specific regional analysis systems for Alzheimer's disease Z‐score (<2 or ≥2) were the dependent variables. Survival curves were obtained by using the Kaplan–Meier estimate. After the log‐rank test, we conducted a Cox proportional hazards regression analysis. Results: The results of log‐rank test indicated that all the variables could significantly influence time to NHP. Cox proportional hazards regression analysis suggested that CDR 3 exhibited the highest hazard ratio and Z‐score showed the lowest hazard ratio. There were significant differences in age, sex, CDR 2, CDR 3, and living situation. Conclusions: The results indicated that the voxel‐based specific regional analysis systems for Alzheimer's disease Z‐score is unlikely to influence NHP. This may suggest that even if the atrophy in the medial temporal lobe is rather progressed, patients can remain living at their own home with protective factors. Future studies need to investigate the risk and protective factors of time to NHP by combining the variables.